Primary Central Nervous System Involvement in Peripheral T-Cell Lymphoma: A Case Report - Seung Hee Byun; Da Mi Kim; In Ho Lee; Chang June Song; Kyung Hwan Kim; Song Yi Choi (대한영상의학회지, 2021)
Primary central nervous system T-cell lymphoma (PCNSTL) is an extremely rare type of brain tumor. There are only few reports on the imaging findings of patients with PCNSTL. Herein, we report the imaging findings of a patient with peripheral T-cell lymphoma-not otherwise specified that presented with numerous small nodular and patchy strongly enhancing lesions on MRI.